Spectrophotometric analysis of crown discoloration induced by MTA- and ZnOE-based sealers - Konstantinos Ioannidis; Ilias Mistakidis; Panagiotis Beltes; Vassilis Karagiannis (University of São Paulo, 2013)
Crown discoloration can be induced by root canal sealer remnants following root canal treatment. Objective: The aim of this study was to evaluate chromatic alterations in human tooth crowns induced by a Mineral Trioxide Aggregate-based sealer (MTA Fillapex®) and a commonly used ZnOE-based sealer (Roth-811). The tested null hypothesis was that the application of the materials did not induce clinically perceptible crown discoloration (Ho: CIE color difference ΔE<3.7). Material and Methods: Forty five fully developed, intact, mandibular third molars were sectioned 1 mm below the cemento-enamel junction. The pulp chambers were chemomechanically debrided via the cervical access. The specimens were randomly assigned into three groups Group 1: MTA Fillapex, Group 2: Roth 811, Group 3: Negative control (unfilled) and immersed in individually marked vials containing distilled water up to the cervix (37±1°C). The spectral reflectance lines were recorded by utilizing a UV-VIS spectrophotometer equipped with integration sphere in the visual spectrum at baseline, 1 week, 1 and 3 months after material placement. Data were transformed into values of the CIE L*a*b* color system and the corresponding ΔE values were calculated. Statistical analysis was performed using two-way mixed ANOVA models, at p=0.05 level of significance. Results: A statistically significant increase in a* and b* chromatic parameters of the MTA Fillapex Group was measured. However, ΔE values did not exceed the human eye perceptibility threshold (set at ΔE<3.7) during the experimental period (ΔEt3=2.88). In Roth-811 Group, a statistically significant decrease in L* and a statistically significant increase in a* and b* chromatic parameters was measured, during all observation periods. Resultant ΔE values exceeded the human eye perceptibility threshold after 1 week (ΔEt1=5.65). Conclusions: Application of MTA Fillapex in tooth crowns resulted in minimal color alterations, while Roth 811 induced severe discoloration, in vitro. It could be suggested that, in terms of aesthetics, the use of MTA Fillapex appears to be favorable.